Inhibition of pancreatic cancer cell growth in vitro by the tyrphostin group of tyrosine kinase inhibitors. - Gillespie, J. (Nature Publishing Group, 1993)
Tyrphostins are a group of low molecular weight synthetic inhibitors of protein tyrosine kinases (PTK). The intracellular domains of the receptors for epidermal growth factor (EGF), transforming growth factor-alpha (TGF-alpha), insulin-like growth factor 1 (IGF-1) possess PTK activity. Since EGF, TGF-alpha and IGF-1 are considered to play an important role in the proliferation of pancreatic cancer cells, we studied the effects of tyrphostins on the growth of three human pancreatic cancer cell lines (MiaPaCa-2, Panc-1 and CAV). The tyrphostins AG17, T23 and T47 all inhibited EGF and serum-stimulated DNA synthesis. AG17 was found to be the most potent of these agents and caused a dose-dependent but reversible inhibition of cell growth. Furthermore using an immunoblotting procedure we also found AG17 to inhibit EGF-induced tyrosine phosphorylation in the MiaPaCa-2 cell line. Tyrosine kinase inhibitors may prove to be useful agents for the treatment of pancreatic cancer. IMAGES: